Palaeomagnetism of the West Sakhalin Basin: evidence for northward displacement during the Cretaceous - Abrajevitch, Alexandra; Zyabrev, Sergey; Didenko, Alexei N.; Kodama, Kazuto (Geophysical Journal International, 2012)
A significant margin-parallel translation of terranes is postulated by all models for tectonic evolution of the East Asian continental margin, although the timing and magnitude of displacements of individual elements are poorly constrained as yet. The West Sakhalin Basin—a forearc basin associated with the Cretaceous volcanic arcs—is one of the displaced tectonic elements. Our palaeomagnetic study of the basin rocks provides the first quantitative constraints on its Cretaceous history. We identified a characteristic magnetization in the Berriasian–Valanginian basalt representing the oceanic basement of the basin and four characteristic magnetizations in a continuous sequence of the Albian to Maastrichtian siliciclastic fill of the basin. A combination of the positive fold, conglomerate and reversals tests supports the primary origin of the remanence in the sediments. Palaeomagnetic data indicate a gradual shift of the West Sakhalin Basin from subequatorial latitudes during the Early Cretaceous to about 40°N by the Late Cretaceous. The main phase of the margin-parallel migration took place during the Early Cretaceous, and ended by the Cenomanian. The continuous sedimentary sequence records ∼50 degrees of progressive clockwise rotation during the Late Cretaceous.